Effect of reward type on object discrimination learning in socially monogamous coppery titi monkeys (Callicebus cupreus). Issue 6 (14th May 2018) - Freeman, Sara M.; Rebout, Nancy; Bales, Karen L.
Abstract : Highly valued food items are often used as rewards to reinforce an animal's behavior. For social species, social interaction is rewarding and can drive an individual's behavior as well. In the currently study, we wanted to compare the efficacy of a food reward and a social reward on object discrimination learning in socially monogamous titi monkeys. We hypothesized that titi monkeys would perform more accurately for a social reward (their pair mate) than for a food reward (a highly desired food item). Eleven adult titi monkeys were tested with a two‐object visual discrimination task for both types of reward. The colors and shapes of the objects in the two‐object discrimination task were counterbalanced across subjects. During each trial, subjects were shown two objects, and the trial ended when the subject touched the reinforced shape (S+) or after 5 min. A correct trial was defined as one when the subject touched S+ first. We found that 45.5% of subjects were able to learn the task with a social reward, and 83.3% were able to learn the task with a food reward. We found that subjects balked more often and had fewer correct trials for the social reward. Finally, subjects took longer to approach the shapes for a social reward, possibly indicating lower motivation to engage in the task when a social reward is used compared to a food reward. Although significantly fewer subjects met criteria of success with the social reward than with the food reward, our results show that titi monkeys can learn a visual discrimination task with either type of reward. Abstract : Coppery titi monkeys can learn a two‐object visual discrimination task using positive reinforcement. These monogamous monkeys perform more accurately and learn the discrimination task faster for a food reward (banana) than a social reward (the return of their pair mate). Despite the strong social bond that a titi monkey has with its pair mate, food is a more effective reinforcing stimulus and motivator than a social reward in tests of learning and cognition in this species.